Increasing Sales Smartly: Kube Wanita Msmes Utilize Gpt Chat As A Promotional Media - Hasanah, Neneng; Napisah, Napisah; Widiyati, Dian (Pasundan Community Service Development, 2024)
Developing effective promotions is crucial for Micro, Small, and Medium Enterprises (MSMEs) in the women's sector of Kube. Leveraging GPT Chat technology presents a streamlined approach for entrepreneurs to craft enticing promotions, thereby boosting sales. Nevertheless, the adoption of such technology faces hurdles due to a lack of awareness among business owners. Recognizing this challenge, lecturers from Pamulang University have initiated a Community Service Program (PKM). Through this program, entrepreneurs are educated on harnessing Chat GPT for promotional purposes. The PKM aims to empower business owners with the requisite skills and knowledge to leverage Chat GPT effectively. Participants undergo comprehensive training sessions where they learn the intricacies of utilizing this technology to enhance their marketing endeavors. As a result of the PKM, MSMEs gain valuable insights into crafting compelling promotions that resonate with their target audience. Furthermore, the program equips participants with strategies to amplify the reach of their promotions, enabling them to tap into broader markets. By embracing innovative solutions like GPT Chat, entrepreneurs can transcend geographical limitations and expand their customer base significantly. Ultimately, the PKM not only enhances the digital capabilities of MSMEs but also fosters economic growth within the women's sector of Kube. Armed with newfound knowledge, these business actors are poised to navigate the evolving landscape of commerce with confidence, driving sustainable success in their ventures.